RELAÇÃO IDENTIDADE/ PERTENCIMENTO CULTURAL NAS COMUNIDADES RIBEIRINHAS DO PARAGUAI MIRIM PANTANAL FRONTEIRIÇO BRASIL-BOLÍVIA - Thayná Cambará Beraldo (2022)
The realization of this research is justified by the need to dialogue with the riverside communities of Paraguay Mirim about the importance of valuing local customs and describing the cultural identity of a people, based on their references, memories and daily activities. The object of this research is the investigation of the existential trajectory of the community of Paraguai Mirim from the years 2020 to 2022, through the analysis of the fragments collected in the various speeches produced by the memorialists regarding the constructed image of the place, and through selected documentation in several archives, such as Acaia Pantanal, Social Assistance Secretariat of the Municipality of Corumbá, Education Secretariat of the Municipality of Corumbá, Foundation for Culture and Historical Heritage of Corumbá, Instituto Homem Pantaneiro, ECOA, which comprises a range of favorable sources for a historic building. In the quest to understand the role of culture as a human development factor in riverside communities, reflecting on memory, identity and cultural belonging within the border Pantanal communities, detailing community identifications in the construction of belonging processes.